Exploring Factors Influencing MOOC Adoption in Afghanistan's Educational Landscape - Musawer Hakimi; Amir Kror Shahidzay; Sebghatullah Aslamzai (International Journal of Scientific Multidisciplinary Research, 2024)
This research investigates the determinants influencing the adoption of Massive Open Online Courses (MOOCs) within the educational landscape of Afghanistan. The study aims to fill a critical gap in the literature by comprehensively exploring the factors shaping MOOC adoption in this specific context. Employing a sample of 133 participants from Kabul University, Balkh University, Samangan University, and Badakhshan University, the study employs a multiple linear regression analysis to assess the impact of technological infrastructure availability, awareness and familiarity with MOOCs, socio-economic factors, and institutional support and government policies on MOOC adoption. The findings reveal a significant positive correlation between technological infrastructure availability and MOOC adoption, emphasizing the pivotal role of robust technological resources. Additionally, heightened awareness and familiarity with MOOCs positively influence adoption, supporting the importance of targeted awareness campaigns. Socio-economic factors, including income levels and urbanization, are identified as influential in shaping MOOC adoption trends. Furthermore, a positive institutional environment and supportive government policies emerge as critical factors facilitating successful MOOC integration